2019
DOI: 10.1101/609370
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RNA-seq analysis of transcriptomes for assessing stress tolerance of S. cerevisiae strain, NCIM3186

Abstract: We have previously sequenced the draft genome of high ethanol producing S. cerevisiae strain, NCIM3186. Towards assessing the stress tolerance by this strain transcriptomes from control and in response to glucose, ethanol and furfural stress were sequenced. Comparative RNA-seq analysis of these transcriptomes identified 573 differentially expressed genes of which thiamine biosynthesis genes under furfural stress, TDH1, heat shock proteins and hexose transporter gene under ethanol stress were observed to be hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Thiamine, or vitamin B1, is an essential nutrient indispensable for the normal growth and development of various organisms, including humans. In yeast, THI13 expression is differentially expressed under low pH values, such as under furfural stress (Goud and Ulaganathan 2019). The involvement of thiamine in the maintenance of the redox balance in yeast cells under oxidative stress by shifting energy generation from fermentation to respiration has been reported elsewhere (Wolak et al 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Thiamine, or vitamin B1, is an essential nutrient indispensable for the normal growth and development of various organisms, including humans. In yeast, THI13 expression is differentially expressed under low pH values, such as under furfural stress (Goud and Ulaganathan 2019). The involvement of thiamine in the maintenance of the redox balance in yeast cells under oxidative stress by shifting energy generation from fermentation to respiration has been reported elsewhere (Wolak et al 2014).…”
Section: Discussionmentioning
confidence: 98%
“…In fact, most of the molecular markers showed increasing trends of correlation with FTIR profiles at increasing ethanol concentrations, confirming the primary role of the FTIR analytical system in finely characterizing the physiological status of cells in various conditions, including stress [ 18 , 49 , 50 , 51 , 52 ]. Several studies have shown that the transcription of TEF-1α can be induced by increasing stressing condition [ 53 , 54 ]. In addition, FAS-1 , one of the main actors in yeast long-chain fatty acid metabolism, was interested in stress response to ethanol [ 55 , 56 ], antifoaming compounds [ 57 ] and high temperature [ 58 ], whereas the mitochondrial COX gene is a known to be part of the cellular response to different types of stressing agents, such as ethanol or high temperatures [ 59 ].…”
Section: Discussionmentioning
confidence: 99%